2004
DOI: 10.1002/cne.20192
|View full text |Cite
|
Sign up to set email alerts
|

Form and function in the unique inner ear of a teleost: The silver perch (Bairdiella chrysoura)

Abstract: Members of the teleost family Sciaenidae show significant variation in inner ear and swim bladder morphology as well as in the relationship between the swim bladder and the inner ear. In the silver perch (Bairdiella chrysoura), a Stellifer-group sciaenid, both the saccular and utricular otoliths are enlarged relative to those in other teleosts. Additionally, its swim bladder is two-chambered, and the anterior chamber surrounds the otic capsule and terminates lateral to the saccules. Structure and function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 54 publications
(81 reference statements)
4
55
0
Order By: Relevance
“…less straightforward than that in cichlids and holocentrids (Ramcharitar et al, 2004(Ramcharitar et al, , 2006Horodysky et al, 2008;Wysocki et al, 2009). Ramcharitar et al (2006) showed that the swim bladder in the weakfish Cynoscion regalis has anterior horns that terminate close to the ears and that this species detects sound frequencies up to 2 kHz.…”
Section: Sciaenidae (Drums and Croakers)mentioning
confidence: 96%
See 4 more Smart Citations
“…less straightforward than that in cichlids and holocentrids (Ramcharitar et al, 2004(Ramcharitar et al, , 2006Horodysky et al, 2008;Wysocki et al, 2009). Ramcharitar et al (2006) showed that the swim bladder in the weakfish Cynoscion regalis has anterior horns that terminate close to the ears and that this species detects sound frequencies up to 2 kHz.…”
Section: Sciaenidae (Drums and Croakers)mentioning
confidence: 96%
“…Surprisingly, both species do not differ in absolute sensitivity, which is rather low (90 dB). In contrast, the silver perch Bairdiella chrysoura has an anterior swim bladder chamber that surrounds the otic capsule and hears up to 4 kHz at thresholds close to that of goldfish (74 dB at 600 Hz; Ramcharitar et al, 2004). Furthermore, Horodysky et al (2008) reported no significant difference in hearing thresholds in species with (Cynoscion regalis, Cynoscion nebulosus, Micropogonias undulatus) and without swim bladder specializations (Sciaenops ocellatus, Leiostomus xanthurus; for a comparison of audiograms see review by Ladich and Fay, 2013).…”
Section: Sciaenidae (Drums and Croakers)mentioning
confidence: 99%
See 3 more Smart Citations